A 22 kW on-board charger for automotive applications based on a modular design - Schmenger, Jens; Endres, Stefan; Zeltner, Stefan; März, Martin (2014 IEEE Conference on Energy Conversion, CENCON 2014, 2014)
In this paper a 22 kW on-board charger for electric or plug-in hybrid vehicles is proposed. To achieve high quantities of devices, a fully modular circuit and control structure is chosen. The circuit arrangement consists of three identical phase units (7.4 kW), which are comprised of two identical (3.7 kW) base units. The proposed charger is implemented and has a volume of 11.1 liters and a weight of 12 kg. The experimental result indicates an efficiency of more than 94 percent over the full battery voltage range at an input voltage of 230 Vac. The output voltage for full load and best efficiency varies from 315-395 V.
CRIS-Team Scopus Importer:2023-03-07
Keywords: battery charger; electric vehicle; energry storage system; plug-in hybrid and power electronics converters